2018
DOI: 10.1111/jpy.12756
|View full text |Cite
|
Sign up to set email alerts
|

The potential for dispersal of microalgal resting cysts by migratory birds

Abstract: Most microalgal species are geographically widespread, but little is known about how they are dispersed. One potential mechanism for long-distance dispersal is through birds, which may transport cells internally (endozoochory) and deposit them during, or in-between, their migratory stopovers. We hypothesize that dinoflagellates, in particular resting stages, can tolerate bird digestion; that bird temperature, acidity, and retention time negatively affect dinoflagellate viability; and that recovered cysts can g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Waterfowl are known to transport viable propagules of other aquatic organisms such as bryozoans, crustaceans and plant seeds (Charalambidou & Santamaría, 2002; Charalambidou et al, 2003; Green et al, 2002). Phytoplankton cysts have also been shown to be able to survive passage in bird guts (Atkinson, 1972; Tesson et al, 2018). Coleman (2001) further suggested that the biogeography of a chlorophyte taxon was followed bird migratory paths.…”
Section: Discussionmentioning
confidence: 99%
“…Waterfowl are known to transport viable propagules of other aquatic organisms such as bryozoans, crustaceans and plant seeds (Charalambidou & Santamaría, 2002; Charalambidou et al, 2003; Green et al, 2002). Phytoplankton cysts have also been shown to be able to survive passage in bird guts (Atkinson, 1972; Tesson et al, 2018). Coleman (2001) further suggested that the biogeography of a chlorophyte taxon was followed bird migratory paths.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being airborne, one possibility for freshwater microalgae to arrive at this tiny coral sand island is to be transported by migratory birds 21 . However, due to the lack of freshwater pond and river, the chance for freshwater birds to stop over on this island is rare.…”
Section: Discussionmentioning
confidence: 99%
“…These can accumulate in the sediments and provide an inoculum for blooms (e.g. Genovesi et al, 2009;Anderson et al, 2014;Mardones et al, 2016), while also facilitating species dispersal via ships' ballast water (Hallegraeff and Bolch, 1991) and/or waterfowl (Tesson et al, 2018). However, before blooming, the non-native species have to pass through several stages to achieve colonization and community maintenance.…”
Section: Introductionmentioning
confidence: 99%